Perceptions of Thai students in commercial art design program at Ubon Teachers' College Ubonrajchathani province, Thailand - Wudthikrai Sirikul 1958-
The purpose of this study is to determine the perception of students in Commercial Art Design Program at the Ubon Teacher College, UbonRajchathani Province, Thailand, towards the program.